The Geographic Context Browser - Krumm, John (First International Workshop on Exploiting Context Histories in Smart Environments (ECHISE 2005), Munich, Germany, 2005)
This paper discusses new techniques for enhancing a sequence of (latitude, longitude) points by tagging them with nearby points of interest and associated Web pages. We present a browser that lets a user explore the enhanced tracks by clicking on a map and filtering over aspects of context.